THE EFFECT OF FEET MASSAGE REFLEXOLOGY ON THE LEVEL OF PAIN ON SECTIO CAESAREA POST SURGERY PATIENTS - Susi Milwati (Health Notions, 2023)
The physiological problems that often arise during the first postoperative day are pain on the former incision. One of the nursing self-care actions for non-pharmacological pain management and is a complementary therapy is a foot reflexology massage. This study aims to determine the effect of foot reflexology treatment on the level of pain in Sectio Caesarea postoperative patients in Masyithoh Islamic Hospital, Bangil. The research method used was Quasy-experiment With Pretest Posttest Control Group Design. Research subjects were postoperative patient of Sectio Caesarea selected with non probability sampling technique of purposive sampling type of 30 respondent, divided into 15 respondents for intervention group and 15 respondents for control group. The average pain level after posttest in the intervention group was in mild pain level and in the control group was in moderate pain level. The Wilcoxon test results showed that there was a difference between pretest and posttest pain levels in both the intervention group and the control group. Mann-Whitney statistical test results showed that there was a difference between posttest pain levels in the intervention group and posttest in the control group with p-value = 0.01 (p <0.05). The conclusion of this research is foot reflexology massage affect the decrease of pain level in postoperative patient of Sectio Caesarea in Masyithoh Islamic Hospital Bangil. It is suggested that nurses should use foot reflexology massage as a complementary therapy because it can reduce pain levels.Keywords: Sectio Caesarea Post Operation; Foot Reflexology Massage; Pain Level